(untitled) (Bangladesh Journal of Zoology, 2019)
The pre-oviposition period of mated and unmated female reared on Bangladeshi and Indian onion was 4.5 ± 0.5, 4.37 ± 0.6 days and 4.11 ± 0.09, 4.45 ± 0.32 days, respectively. The oviposition period of mated and unmated female was 5.6 ± 0.6, 6.03 ± 0.6 days and 6.48 ± 0.39, 6.5 ± 0.34 days reared on Bangladeshi and Indian onion, respectively. The life cycle of Delia antiqua consisted of four definite stages: egg, larva, pupa and adult. The incubation period was1.38 ± 0.11 and 1.25 ± 0.05 days; larval period was 5.7 ± 0.7 and 5.4 ± 0.05 days; pupal period was 6.8 ± 0.2 and 6.08 ± 0.2 days, respectively. There were three larval instars in D. antiqua. To complete the total life cycle it required shorter period in Indian than in Bangladeshi onion. The total life cycle of female was 16.73 ± 0.89 and 15.29 ± 0.45 days, respectively on Bangladeshi and Indian onion. The difference between the life cycle of female was significant (p < 0.05) in Bangladeshi and Indian onion. Fecundity was higher in Indian than in Bangladeshi onion. The fecundity of female D. antiqua reared in Bangladeshi and Indian onion was 75.2 ± 4.09 and 89.2 ± 2.39, respectively and it was significantly (p < 0.05) varied. Female lived longer than male D. antiqua. It was more susceptible in Indian than Bangladeshi onion irrespective of the duration of life cycle and fecundity. Bangladesh J. Zool. 47(2): 325-332, 2019